PERBUATAN MANUSIA DALAM PANDANGAN AL-ASY’ARIY - Fuad Mahbub Siraj (Universitas Paramadina, 2013)
AbstractThe Discourse of human activity is one of the crucial issues in Islamictheology. This discourse is occupied a significant position because it wasconcerned with the issue, how far the human will is influence to theiractivities that ultimately human responsibility is closely related to theiractivities. Al-Asy’ariy use the term of al-Kasb that understood as the rightterm to describe the relation between human and their activity. Kasbaccording to al-Asy’ariy is the activity that come from human through thepower that created by Allah. The iradah of human is just paled to the willand tendency but cannot realize the act. Otherwise, it is only the iradah ofAllah that able to create human activity and this iradah of Allah is effectiveto create human activity or give kasb to human and includes everything thatexists.